2019
DOI: 10.1021/acsaem.9b01384
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Efficiency and Stability of NiOx-Based Silicon Photoanode via Interfacial Engineering

Abstract: The photoelectrochemical performance of Si photoanode with a metal–insulator–semiconductor (MIS) structure is limited by weak Schottky barrier and poor charge transfer. In this work, a MIS structure, n-Si|dispersed NiSi x /NiO x patches|Au nanoparticles, is designed for efficient water oxidization with high stability. The photoanode exhibits a high activity with a low onset potential of ∼0.88 V and a high photocurrent density of ∼34 mA/cm2 at 1.23 V versus reversible hydrogen electrode (RHE), and retains exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…One design strategy to generate a large barrier height and photovoltage in MIS systems is to use high work function metals for n‐type systems (low work function metals for p‐type systems) 49,52,56. Another strategy to obtain a large barrier height is through the pinch‐off effect, where a high barrier electrolyte or oxide can compensate for low barrier electrocatalytic metal nanoparticles 29,32,34,40,41,57. Previous reports have also demonstrated that the insulator layer can serve as a passivation layer to remove defects and minimize barrier height losses from Fermi level pinning 50,51,53.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One design strategy to generate a large barrier height and photovoltage in MIS systems is to use high work function metals for n‐type systems (low work function metals for p‐type systems) 49,52,56. Another strategy to obtain a large barrier height is through the pinch‐off effect, where a high barrier electrolyte or oxide can compensate for low barrier electrocatalytic metal nanoparticles 29,32,34,40,41,57. Previous reports have also demonstrated that the insulator layer can serve as a passivation layer to remove defects and minimize barrier height losses from Fermi level pinning 50,51,53.…”
Section: Introductionmentioning
confidence: 99%
“…[49,52,56] Another strategy to obtain a large barrier height is through the pinch-off effect, where a high barrier electrolyte or oxide can compensate for low barrier electrocatalytic metal nanoparticles. [29,32,34,40,41,57] Previous reports have also demonstrated that the insulator layer can serve as a passivation layer to remove defects and minimize barrier height losses from Fermi level pinning. [50,51,53] Furthermore, several studies have shown that annealing is an effective method to further passivate interfacial defects and improve the photovoltage.…”
mentioning
confidence: 99%
“…The free energy diagrams of OER at 0 V versus CHE are also provided in Supplementary Fig. 23. In addition, the reaction kinetics of Ir SAs/NiO (100) was examined to predict the kinetic barrier heights of the ratedetermining step via climbing image nudged elastic band (CI-NEB) calculations in Supplementary Fig.…”
Section: Theoretical Investigations On Ir Sas/nio Pec Catalystsmentioning
confidence: 99%
“…Here, we report an atomic-scale-architectured Ir SAs/NiO/Ni/ ZrO 2 /n-Si photoanode device with drastically enhanced catalytic activity and stability. The NiO/Ni, which is highly catalytic and stable in alkaline condition, intrinsically has lots of Ni vacancies suitable for stabilization of single atoms [20][21][22][23][24] . As a result, it is possible to utilize the thin-film NiO/Ni as both a PEC catalyst and anchoring layer to capture metal atoms.…”
mentioning
confidence: 99%
“…Great effort has been focused on the integration of Si with a catalyst to improve the charge transfer kinetics and protect the semiconductor–electrolyte interface from corrosion. Coating the Si surface with transition metals, e.g., Co, Ni, Fe, and their composites or oxides has shown to efficaciously catalyze oxygen evolution reaction and protect Si from corrosion. …”
Section: Introductionmentioning
confidence: 99%